Pik3ca mutations significantly enhance the growth of SHH medulloblastoma and lead to metastatic tumour growth in a novel mouse model. (1st May 2020) - Niesen, Judith; Ohli, Jasmin; Sedlacik, Jan; Dührsen, Lasse; Hellwig, Malte; Spohn, Michael; Holsten, Till; Schüller, Ulrich
Abstract: Medulloblastoma (MB) is the most frequent malignant brain tumour in children with a poor outcome. Divided into four molecular subgroups, MB of the Sonic hedgehog (SHH) subgroup accounts for approximately 25% of the cases and is driven by mutations within components of the SHH pathway, such as its receptors PTCH1 or SMO . A fraction of these cases additionally harbour PIK3CA mutations, the relevance of which is so far unknown. To unravel the role of Pik3ca mutations alone or in combination with a constitutively activated SHH signalling pathway, transgenic mice were used. These mice show mutated variants within Smo, Ptch1 or Pik3ca genes in cerebellar granule neuron precursors, which represent the cellular origin of SHH MB. Our results show that Pik3ca mutations alone are insufficient to cause developmental alterations or to initiate MB. However, they significantly accelerate the growth of Shh MB, induce tumour spread throughout the cerebrospinal fluid, and result in lower survival rates of mice with a double Pik3caH1047R/SmoM2 or Pik3caH1047R/Ptch1 mutation. Therefore, PIK3CA mutations in SHH MB may represent a therapeutic target for first and second line combination treatments. Highlights: PIK3CA mutations represent frequent alterations in MB, particularly in SHH MB. Pik3ca mutations contribute to MB tumour growth. Pik3ca mutations lead to metastatic tumour growth in brain and spinal cord. PIK3CA might represent a therapeutic target for MB in future studies.